Deriving of the Standard Machine Name Programmatically A Study from the Perspective of Computational Languages - Mohammed, Mohammed; Sagheer , Ali (Islamic Sciences Journal, 2023)
This paper is a joint research between linguistic sciences and applied computer sciences, in order to introduce the linguistic phenomenon to digital computer science within what is known as (computational languages). The paper dealt with making a computer program to derive the Arabic machine's name in standard derivation with all its morphological fluctuations, whether It is the correct or the faulty one. The applied technique has been able to program the morphological law in a computerized algorithmic technique. So that it performs the exchange process and its requirements of explaining or substituting or others, as it simulates the user of the Arabic language in the production of an infinite number of standard machine names according to what the program user enters. This step is a confident beginning, Allah Almighty willing, for new programs in the service of Arabic language : studying, teaching and using.